Operação em paralelo e sem comunicação de sistemas UPS: uma abordagem baseada em passividade - Marcelo de Azevedo Avila (2013)
Parallelism of voltage sources is a recurring and important problem in Electrical Engineering area. In the recent context of smart grids or in UPS systems (Uninterruptible Power Supplies), the availability of two or more energy sources increases the robustness and reliability of electric system. Among the parallelism techniques there are those which do not make use of any informations exchange between the sources, a characteristic that eliminates the need for a dedicated communication channel and, consequently, the existence of a single point of failure. In the present work is investigated the digital implementation of an approach to parallel operation of UPS without communication. The method is developed in time domain and it relies on the natural tendency to synchronization of interconnected incrementally dissipative nonlinear oscillators. Simulations of two interconnected UPS systems to a given linear electric network are carried out, taking into consideration specific problems associated with the practical implementation in a Digital Signal Processor (DSP) based system. Practical tests conducted in laboratory demonstrate the feasibility of synchronism technique studied, whose results are even more embracing than the current scope covered by the theory. To improve the transient behavior of parallelism of voltage sources, is developed a pre-synchronism methodology based on state observer. Simulations and experimental results demonstrate the efficiency of the proposed methodology.